The Salesians of Don Bosco a historical study of the organization, with emphasis on its educational practices in the Philippines - Fajardo, Florencio 1924- ([Quezon City s.n.], 1964)
The Salesians of Don Bosco, the name which the male members of the Salesian Society has been popularly known of, is the subject of this study. Emphasis was laid on their role as educators because the main purpose of this study is to find out how they practice pedagogy among the Filipinos.
Thesis (M.Ed.)--University of the Philippines
Keywords: Salesians -- Education; Salesians in the Philippines